ASSESSMENT OF WATER DEMANDS IN THE RURAL SETTLEMENTS OF THE SOMEŞEAN PLATEAU - V. SOROCOVSCHI; HORVÁTH Cs (Aerul şi Apa: Componente ale Mediului, 2011)
Assessment of water demands in the rural settlements of theSomeşan Plateau. Through this paper we have evaluated four different waterdemand calculations, which would allow the development of water supplystrategies on a short, medium and long term. Judging by the second variant ofcalculation the total water needs of the localities, from the Someşean Plateau,ranges from 40,9 l/s, for the first variant, to 199,4 l/s, in case of the second variant.Water demand was estimated at administrative level (district, commune andlocalities), for the main river basins and their related sub-basins, and also on ageographical sub-units level. Regardless of the variant we used when calculatingthe weight of units or analyzed subunits, this remains the same. For example, theCluj County holds 66.5% of the necessary water in the Someşean Plateau,followed by the counties of Sălaj and Maramureş with 28.8% and 5.7%. The riverbasins of Someş and Someşul Mic represent approximately equal weights (48.3%and 48.6%), while the basin of Lăpuş is defined by a very small percentage. Theshare that defines different administrative subunits, either geographical orhydrographical, depends on the area, density and size of the related localities. Theshare of water that belongs to each geographic subunit from the Someşean Plateauranges between 33.8% (in the Cluj Hills) and 6.3% (in the Sălătruc Hills). Thewater volumes required annually by the Someşean Plateau localities oscillatesbetween 1288 m3, in the first case scenario and 6281 m3 in the fourth case. So, theevaluated water volumes should be decreased, on average, by about 30%,depending on the specific circumstances of the territories studied by taking intoaccount the unfavorable position of some towns to the main hydrographicalcourse, the size of settlements, as well as the opportunities of their futuredevelopment.